Pemanfaatan Tepung Umbut Kelapa Sawit (Elaeis Guineensis Jacq) dan Ikan Lele (Clarias Sp) sebagai Inovasi Pangan Tinggi Serat dan Protein untuk Pencegahan Risiko Diabetes Melitus - Alfira Alfira; Oslida Martony; Rizky Ayu Febbyana; Hotma Raskita Siregar; Agil Adis Abiba (Institut Penelitian Matematika, Komputer, Keperawatan, Pendidikan dan Ekonomi (IPM2KPE), 2026)
This study aimed to analyze the acceptability of food products based on palm oil and catfish flour, including biscuits, nuggets, and sticks, and their potential as functional foods for the prevention of diabetes mellitus. The study used a completely randomized experimental design (CRD). The results showed that products formulated with palm oil and catfish flour were well-accepted by panelists. The biscuits demonstrated the highest scores for aroma (3.76), color (3.68), texture (3.62), and taste (3.68). The nugget and stick products also demonstrated high levels of preference for formulations containing moderate amounts of palm oil flour. ANOVA analysis showed significant differences between treatments (p<0.05). In conclusion, the combination of palm oil and catfish flour can produce high-fiber and protein food products that have the potential to support the prevention of diabetes mellitus by increasing dietary fiber consumption. Keywords: Diabetes Mellitus, Catfish, Functional Food, Dietary Fiber, Palm Oil Flour